Mortality tradeoff between air quality and skin cancer from changes in stratospheric ozone. (9th March 2018) - Eastham, Sebastian D; Keith, David W; Barrett, Steven R H
Abstract: Skin cancer mortality resulting from stratospheric ozone depletion has been widely studied. Similarly, there is a deep body of literature on surface ozone and its health impacts, with modeling and observational studies demonstrating that surface ozone concentrations can be increased when stratospheric air mixes to the Earth's surface. We offer the first quantitative estimate of the trade-off between these two effects, comparing surface air quality benefits and UV-related harms from stratospheric ozone depletion. Applying an idealized ozone loss term in the stratosphere of a chemistry-transport model for modern-day conditions, we find that each Dobson unit of stratospheric ozone depletion results in a net decrease in the global annual mortality rate of ~40 premature deaths per billion population (d/bn/DU). The impacts are spatially heterogeneous in sign and magnitude, composed of a reduction in premature mortality rate due to ozone exposure of ~80 d/bn/DU concentrated in Southeast Asia, and an increase in skin cancer mortality rate of ~40 d/bn/DU, mostly in Western Europe. This is the first study to quantify air quality benefits of stratospheric ozone depletion, and the first to find that marginal decreases in stratospheric ozone around modern-day values could result in a net reduction in global mortality due to competing health impact pathways. This result, which is subject to significant methodological uncertainty, highlights the need to understand the health and environmental trade-offs involved in policy decisions regarding anthropogenic influences on ozone chemistry over the 21st century.